Accounting for the cost of social media. Issue 3 (4th November 2014) - A. Crumpton, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to discuss the importance of identifying the cost associated with using social media for library marketing efforts, as well as assessing the effectiveness of social media activities. Design/methodology/approach – This paper references articles and trends on this topic. Findings – With an increase in use of social media activities within libraries, there is clear evidence that creating formal assessment practices and tracking expenditures provides an increase in effectiveness and efficiency of those activities. Originality/value – This paper is written from the author's own perceptions and actions taken on this topic.